Characteristics and Applications of CAAC-IGZO FET with Gate Length of 13nm. (8th September 2020) - Suzuki, Akio; Yuichi, Yanagisawa; Mizukami, Shota; Tsuda, Kazuki; Ito, Minato; Ohshima, Kazuaki; Matsumoto, Noriko; Yakubo, Yuto; Miyata, Shoki; Okuno, Naoki; Kunitake, Hitoshi; Sasagawa, Shinya; et al.
Abstract : A field-effect transistor (FET) with a gate length of 13 nm having a c -axis aligned crystalline In-Ga-Zn oxide (CAAC-IGZO) channel was fabricated. The CAAC-IGZO FET has an off-state leakage current of 200 yA/μm, a cutoff frequency of 60GHz, and a maximum oscillation frequency of 16GHz. A CAAC-IGZO FET, though it is a small transistor, withstands voltages up to approximately 2.5 V. It also has stable current characteristics with less temperature dependence than Si devices. We have constructed an equivalent-circuit model of the CAAC-IGZO FET and designed an RF amplifier to show CAAC-IGZO FET's applicability to the GHz-range RF circuitry.